Acute Migraine Therapy: New Drugs and New Approaches - Monteith, Teshamae S. (Current Science Inc., 2010)
The conceptual shift of our understanding of migraine from a vascular disorder to a brain disorder has dramatically altered the approach to the development of new medicines in the field. Current pharmacologic treatments of acute migraine consist of nonspecific and relatively specific agents. Migraine-specific drugs comprise two classes, the ergot alkaloid derivatives and the triptans, serotonin 5-HT(1B/1D) receptor agonists. The ergots, consisting of ergotamine and dihydroergotamine (DHE), are the oldest specific antimigraine drugs available and are considered relatively safe and effective. Ergotamine has been used less extensively because of its adverse effects; DHE is better tolerated. The triptan era, beginning in the 1990s, was a period of considerable change, although these medicines retained vasoconstrictor actions. New methods of delivering older drugs include orally inhaled DHE and the transdermal formulation of sumatriptan, both currently under study. Novel medicines being developed are targeted at neural sites of action. Serotonin 5-HT(1F) receptor agonists have proven effective in phase II studies and have no vascular actions. Calcitonin gene-related peptide (CGRP) receptor antagonists are another promising nonvasoconstrictor approach to treating acute migraine. Olcegepant (BIBN4096BS) and telcagepant (MK-0974) have been shown to be safe and effective in phase I, II, and (for telcagepant) phase III clinical trials. Other targets under investigation include glutamate (AMPA/kainate), TRPV1, prostanoid EP4, and nitric oxide synthase. With new neural targets and the potential for therapeutic advances, the next era of antimigraine medications is near.